ANALISIS KARAKTERISTIK LIMBAH PABRIK GULA (BLOTONG) DALAM PRODUKSI BAHAN BAKAR GAS (BBG) DENGAN TEKNOLOGI ANAEROB BIODIGESTER SEBAGAI SUMBER ENERGI ALTERNATIF NASIONAL - Heni Dwi Kurniasari; Rahilla Apria Fatma; Janser Aldomoro S R (Jurnal Sains & Teknologi Lingkungan, 2019)
Blotong is a solid waste produced from a refining station with a filtering mechanism for dirty sap in a vacuum filter with dirty roomie on a door clarifier, which has been added with additional ingredients. Blotong waste processing with digestion technology in the manufacture of new renewable energy is a very effective and efficient solution. The digestion process can run optimally, effectively and efficiently with regard to the content of C / N ratio, temperature, pH, and other supporting factors. The raw materials used are blotong from PT. Madu Baru Madukismo Yogyakarta. The raw material is mixed with cow dung and inoculum as a starter in the process of breeding methane bacteria. After all the ingredients are mixed then put in a reactor called a digester with a fermentation time of 50 days and an observation of the temperature, production, and content of methane in biogas is carried out. The materials put in the reactor varied with the composition of the blotong and cow manure, namely: 100%: 0%, 90%: 10%, 80%: 20%, 70%: 30%, 60%: 40%, 50%: 50 %. As for the inoculum as a starter in the biogas process, 30% of the total volume of the material is included. The purpose of this study is expected to be able to produce biogas with the optimal amount and quality of gas as an alternative fuel for the community